Childhood Experiences and Psychological Distress: Can Benevolent Childhood Experiences Counteract the Negative Effects of Adverse Childhood Experiences? - Hou, Hao; Zhang, Caochen; Tang, Jie; Wang, Jingjing; Xu, Jiaqi; Zhou, Qin; Yan, Wenjun; Gao, Xiuyin; Wang, Wei (Frontiers in Psychology, 2022)
Abstract Background Childhood experiences can exert a huge impact on adult psychological conditions. Previous studies have confirmed the effects of adverse childhood experiences (ACEs) and benevolent childhood experiences (BCEs) on psychological distress (stress, depression, and suicidal ideation) separately, but few studies explored a combined effect of them on psychological distress. Our study aims to explore a combined effect of ACEs and BCEs on psychological distress among Chinese undergraduates. Methods Participants were undergraduates aged 17-24 years (N=1816) who completed a self-reported questionnaire. A series of regression analyses were conducted to examine the association between childhood experiences and psychological distress. Results A total of 65.7% of undergraduates had BCEs and 27.1% of undergraduates reported ACEs, while 12.9% of undergraduates reported ACEs and BCEs simultaneously. Logistic regression analysis indicated that undergraduates who experienced High ACEs were more likely to have a high risk of psychological distress (ORs=1.46,1.84, 3.15 for uncertainty stress, depressive symptoms, and suicidal ideation, respectively) while undergraduates who experienced High BCEs were less likely to have psychological distress (ORs=0.33,0.22, 0.32 for uncertainty stress, depressive symptoms, and suicidal ideation, respectively) compared with Low-Both group. The combined effect of ACEs and BCEs (High Both group) could also play as a protective factor in uncertainty stress (OR=0.56) and depressive symptoms (OR=0.47). Conclusions Our findings suggested that ACEs and BCEs could not only predict the psychological distress independently, but also BCEs could counteract the negative effect of ACEs in psychological problems. There is an even greater need to identify and support victims of ACEs, and increase BCEs in early childhood.